Strategi Proses Perencanaan Content Planning Media Sosial TikTok @Garudasystrain.id - Raisha Maharani; Aceng Hidayat (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the content planning process and strategy on the TikTok account @Garudasystrain.id managed by PT Garuda Systrain Interindo. Using a qualitative descriptive approach through observation, interviews, literature review, and active participation during six months of Field Work Practice (PKL), this study describes how the company structures its social media workflow to support educational communication in the field of Occupational Safety and Health (K3). The results show that the content planning process is carried out through systematic stages, starting from trend research, idea gathering, content planning sheet preparation, upload scheduling, approval process, and weekly collaboration between team members. These stages ensure that the resulting content is relevant, consistent, and in line with the company's educational objectives. In addition, the content strategy is structured based on the Hierarchy of Effects Model, which includes the stages of awareness, knowledge, liking, preference, conviction, and action, so that the message delivery flow can encourage the audience from recognition to action. The use of clear and targeted Call to Action (CTA) also strengthens interaction and encourages audience participation. Overall, this approach helps PT Garuda Systrain Interindo in using TikTok strategies, improving the company's image, and strengthening the effectiveness of digital communications related to K3.